2012
DOI: 10.1002/iub.1043
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular mechanisms involved in the trypanosoma cruzi/host cell interplay

Abstract: SummaryThe protozoan parasite Trypanosoma cruzi has a complex bi-ological cycle that involves vertebrate and invertebrate hosts. In mammals, the infective trypomastigote form of this parasite can invade several cell types by exploiting phagocytic-like or non-phagocytic mechanisms depending on the class of cell involved. Morphological studies showed that when trypomastigotes contact macrophages, they induce the formation of plasma membrane protrusions that differ from the canonical phagocytosis that occurs in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…According to the SNARE model, it is expected that SNAREs involved in TcPV formation would be displayed on its limiting membrane as a result of fusion events (Bombardier & Munson, 2015). For this reason, we investigated the presence of three different v-SNAREs based on their role in trafficking pathways previously related with T. cruzi host cell entry (Romano et al, 2012).…”
Section: V-snares From the Endocytic Pathway Are Recruited To The Tmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the SNARE model, it is expected that SNAREs involved in TcPV formation would be displayed on its limiting membrane as a result of fusion events (Bombardier & Munson, 2015). For this reason, we investigated the presence of three different v-SNAREs based on their role in trafficking pathways previously related with T. cruzi host cell entry (Romano et al, 2012).…”
Section: V-snares From the Endocytic Pathway Are Recruited To The Tmentioning
confidence: 99%
“…Studies of the mechanism that allows trypomastigotes (Try), the infective stage of T. cruzi, reaching host cell lysosomes in nonprofessional phagocytic cells have disclosed different strategies (Romano et al, 2012). The first involves lysosomes exocytosis at the site of parasite attachment (Tardieux et al, 1992), suggesting that lysosomes provide the membrane required for TcPV formation.…”
Section: Introductionmentioning
confidence: 99%
“…Epimastigote and amastigote are the replicative stages of the insect vector and mammalian host (De Souza, 2002), respectively. Since its discovery by Carlos Chagas, more than a century ago, it has been assumed that epimastigotes are not infective to the mammalian host (Chagas, 1909;Romano et al, 2012). This paradigm is corroborated by the widely acknowledged fact that only the epimastigote stage is susceptible to the mammalian innate immunity system and can be killed by the complement system (Nogueira et al, 1975;Iida et al, 1989;Cestari et al, 2009;Cestari and Ramirez, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This transport is dependent on the KIF 5 protein (a kinesin) [76]. More recently, Romano et al [77] have shown that an autophagic protein, LC3, would also be present in the PV membrane, also demonstrating that the induction of autophagy in the host cell (pharmacological or physiological) interferes with the mechanism of trypomastigote invasion. Autophagy mechanism also plays a protective role against T. cruzi infection in mice by activation of a host immune response [78].…”
Section: Mechanisms Of Internalization Of Trypanosoma Cruzi Trypomastmentioning
confidence: 99%